(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This research paper delves into the issue of women criminality in India, with a particular focus on the state of Uttarakhand. The selection of Uttarakhand as the research area is motivated by the alarming number of crimes reported in the Himalayan states, with recent data from the National Crime Records Bureau (NCRB) highlighting a significant increase in rape and child abuse incidents in the region. This surge in crime has drawn widespread attention from the public, necessitating a closer examination of the role played by women criminals in contributing to this rise.